Direct probing of atomically dispersed Ru species over multi-edged TiO2 for highly efficient photocatalytic hydrogen evolution - Zhang, Huabin (2020)
A cocatalyst is necessary for boosting the electron-hole separation efficiency and accelerating the reaction kinetics of semiconductors. As a result, it is of critical importance to in situ track the structural evolution of the cocatalyst during the photocatalytic process, but it remains very challenging. Here, atomically dispersed Ru atoms are decorated over multi-edged TiO2 spheres for photocatalytic hydrogen evolution. Experimental results not only demonstrate that the photogenerated electrons can be effectively transferred to the isolated Ru atoms for hydrogen evolution but also imply that the TiO2 architecture with multi-edges might facilitate the charge separation and transport. The change in valence and the evolution of electronic structure of Ru sites are well probed during the photocatalytic process. Specifically, the optimized catalyst produces the hydrogen evolution rate of 7.2 mmol g-1 hour-1, which is much higher than that of Pt-based cocatalyst systems and among the highest reported values.